2016
DOI: 10.1659/mrd-journal-d-15-00111.1
|View full text |Cite
|
Sign up to set email alerts
|

Does Agrotourism Benefit Mountain Farmers? A Case Study in Phu Ruea District, Northeast Thailand

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
1
13
0
8
Order By: Relevance
“…A pesar de todo, resulta difícil encontrar referencias que traten la agricultura como producto turístico, aunque es posible diferenciar dos tendencias claras de estudios que analizan los vínculos que se establecen entre los dos sectores: los que tratan sobre los impactos generados por el desarrollo del turismo en la agricultura (Hermans, 1981;Torres, 2003;Torres y Momsen, 2004;Choenkwan et al, 2016) y los que se ocupan de la influencia que tiene la agricultura en el sistema turístico (Duarte Alonso, 2010;Anderson, 2018). También se detectan otros enfoques minoritarios centrados en el desarrollo económico y en la sostenibilidad agraria desde una perspectiva "agroecológica" como base del agroecoturismo (Kuo et al, 2008), e incluso los que hacen referencia a la multifuncionalidad de la agricultura (Brandth y Haugen, 2011) y de las áreas rurales (Aznar et al, 2007) con el aprovechamiento de los recursos agrarios y rurales para el turismo.…”
Section: Discussionunclassified
“…A pesar de todo, resulta difícil encontrar referencias que traten la agricultura como producto turístico, aunque es posible diferenciar dos tendencias claras de estudios que analizan los vínculos que se establecen entre los dos sectores: los que tratan sobre los impactos generados por el desarrollo del turismo en la agricultura (Hermans, 1981;Torres, 2003;Torres y Momsen, 2004;Choenkwan et al, 2016) y los que se ocupan de la influencia que tiene la agricultura en el sistema turístico (Duarte Alonso, 2010;Anderson, 2018). También se detectan otros enfoques minoritarios centrados en el desarrollo económico y en la sostenibilidad agraria desde una perspectiva "agroecológica" como base del agroecoturismo (Kuo et al, 2008), e incluso los que hacen referencia a la multifuncionalidad de la agricultura (Brandth y Haugen, 2011) y de las áreas rurales (Aznar et al, 2007) con el aprovechamiento de los recursos agrarios y rurales para el turismo.…”
Section: Discussionunclassified
“…In the study conducted by Choenkwan et al (2016) in Thailand, it was determined that 1500 people in Phu Ruea district participated in agricultural tourism activities and 90% of them were farmers or family members of farmers. In the study, it was determined that agricultural tourism activities increased farmer income and quality of life of farmers.…”
Section: Discussionmentioning
confidence: 99%
“…The government is trying to increase economic development in these islands by the promotion of "agro-tourism linkages" which have multiple benefits to both sectors. Choenkwan et al, 2016 have reported on the impacts of agro-tourism to mountain farmers. The authors mentioned that the relationship between agriculture and tourism is complex and the extent to which tourism benefits farmers remains uncertain.…”
Section: Agro-tourismmentioning
confidence: 99%